Features of local oral immunity in patients with generalized periodontitis and concomitant systemic diseases - Борисенко, Анатолій Васильович; Коленко, Юлія Геннадіївна; Линовицька, Олеся Вікторівна; Несін, Олександр Федорович; Тімохіна, Тетяна Олександрівна; Печковський, Костянтин Євгенович (Actual Dentistry, 2019)
Abstract. Dystrophic-inflammatory processes in periodontium may be the first clinical signs of disorders in the presence of various systemic diseases. The prevalence and intensity of periodontal disease increases in proportion to the duration and severity of the underlying systemic disease. Among these diseases, our attention was attracted to bronchial asthma and arterial hypertension. Objective: is to determine indicators of local immunity in patients with generalized periodontitis with various general somatic diseases (bronchial asthma and arterial hypertension). Materials and research methods. To achieve this aim 118 patients with generalized periodontitis II grade aged from 42 to 60 years old were examined. Patients were divided into groups: First (1) group were consisted of 37 patients with generalized periodontitis and persistent bronchial asthma. Second (2) group were consisted of 39 patients with generalized periodontitis with concomitant arterial hypertension. All patients underwent immunological xamination to determine the level of pro- and anti-inflammatory cytokines in blood serum and saliva, the level of circulating immune complexes, the concentration of immunoglobulins IgG, IgA, IgM, IgE in serum and secretory sIgA in saliva, the phagocytic activity of peripheral blood neutrophils and phagocytes in the saliva. Results. In patients with generalized periodontitis with concomitant bronchial asthma were found pro-inflammatory changes in the humoral link of the immune system, decreased phagocytic activity of peripheral blood neutrophils and pronounced signs of immunotoxicosis. In the saliva were detected increase level of IgG, IL-4 and a significant decrease concentration of SIgA, IFN-γ. Patients with generalized periodontitis and concomitant arterial hypertension showed an imbalance in the level of CICs with a significantly reduced content of physiological CICs of a large size and an increased level of pathogenic medium and low molecular CICs. A significant increase in the level of pro-inflammatory TNF-α, IL-1β, IL-6 and a significant decrease in the concentration of IL-4 were revealed in the saliva. Conclusions. In patients with generalized periodontitis with concomitant bronchial asthma, were detected pro-inflammatory changes in the humoral link of the immune system (blood, saliva). Changes in the indices of local immunity of the saliva are deeper and more specific in comparison with patients with arterial hypertension, where they have the character of subclinical atherosclerotic inflammation. Key words: generalized periodontitis, local immunity, cytokines, saliva, secretory immunoglobulin A, circulating immune complexes.